Sustainability and Climate Risk Data: A New Era for Investment Decision Making in the Age of Climate Change - MARCZISDávid; MIHÁLOVITSZsolt; SEBESTYÉNGéza (Cognitive Sustainability, 2022)
As economic actors face increasing pressure to be socially responsible and environmentally conscious, investors look beyond traditional financial metrics and seek data to support their decision-making. Measuring and reporting sustainability and climate risks is a relatively new discipline with several interrelations to economic, financial, risk management, and other cognitive study areas such as climate sciences, and have come a long way in the last couple of years. We are in the middle of the evolutionary process, as data availability and coverage are much better than a decade ago. However, there is still a lot to do until the new metrics and indicators are fully embedded in risk management frameworks and decision-making processes, similar to traditional risk measures. In our essay, we will explore the role of third-party data vendors for sustainability, ESG, and climate risk-related information, their importance in the modern investing world, and review the major challenges. We give an insight into the evolution of the market of data vendors and also the regulatory landscape. Finally, we explore the unique roles of central banks and their challenges in implementing actions in sustainability.